Monetary policy, global liquidity and commodity price dynamics - Ansgar Belke; Ingo G. Bordon; Torben W. Hendricks (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper examines the interactions between money, interest rates, goods and commodity prices at a global level. For this purpose, we aggregate data for major OECD countries and follow the Johansen/Juselius cointegrated VAR approach. Our empirical model supports the view that, when controlling for interest rate changes and thus different monetary policy stances, money (defined as a global liquidity aggregate) is still a key factor to determine the long-run homogeneity of commodity prices and goods prices movements. The cointegrated VAR model fits with the data for the analysed period from the 1970s until 2008 very well. Our empirical results appear to be overall robust since they pass inter alia a series of recursive tests and are stable for varying compositions of the commodity indices. The empirical evidence is in line with theoretical considerations. The inclusion of commodity prices helps to identify a significant monetary transmission process from global liquidity to other macro variables such as goods prices. We find further support of the conjecture that monetary aggregates convey useful information about variables such as commodity prices which matter for aggregate demand and thus inflation. Given this clear empirical pattern it appears justified to argue that global liquidity merits attention in the same way as the worldwide level of interest rates received in the recent debate about the world savings and liquidity glut as one of the main drivers of the current financial crisis, if not possibly more.
Keywords: E31; E52; C32; F42; 330; Commodity prices; cointegration; CVAR analysis; global liquidity; inflation; international spillovers; Geldpolitik; Gesamtwirtschaftliche Liquidität; Transmissionsmechanismus; Rohstoffpreis; Spillover-Effekt; Inflation; Kointegration; Schätzung; OECD-Staaten